A Compact Fluorescence System for Tumor Detection: Performance and Integration Potential - Jean Pierre Ndabakuranye; John Raschke; Preston Avagiannis; Arman Ahnood (Biosensors)
Fluorescence-guided surgery (FGS) is an innovative technique for accurately localizing tumors during surgery, particularly valuable in brain tumor detection. FGS uses advanced spectral and imaging tools to provide precise, quantitative fluorescence measurements that enhance surgical accuracy. However, the current challenge with these advanced tools lies in their lack of miniaturization, which limits their practicality in complex surgical environments. In this study, we present a miniaturized fluorescence detection system, developed using state-of-the-art CMOS color sensors, to overcome this challenge and improve brain tumor localization. Our 3.1 × 3 mm multispectral sensor platform measures fluorescence intensity ratios at 635 nm and 514 nm, producing a high-resolution fluorescence distribution map for a 16 mm × 16 mm area. This device shows a high correlation (R2 > 0.98) with standard benchtop spectrometers, confirming its accuracy for real-time, on-chip fluorescence detection. With its compact size, our system has strong potential for integration with existing handheld surgical tools, aiming to improve outcomes in tumor resection and enhance intraoperative tumor visualization.